Driving Factors and Feasibility Analysis: China–Mongolia Collaboration on Climate Change under the Belt and Road Initiative Framework - Pin Zuo; Zolboo Dashnyam; Ping Jiang (The Mongolian Journal of International Affairs)
The Belt and Road Initiative (BRI) offers great opportunities for China and Mongolia to collaborate on tackling climate change. However, few studies have focused on China–Mongolia collaboration on climate change under the BRI’s sustainable development framework; in particular, studies have neglected the factors and feasibility of collaboration. Focusing on China and Mongolia, this study first discusses the evolution of legislation in China and Mongolia in the context of dealing with climate change and then explores the factors that influence China–Mongolia collaboration on climate change mitigation from the perspectives of climate environmental governance and energy development at the domestic level. Subsequently, the paper analyzes the Paris Agreement to identify international factors that can influence climate change cooperation between the two countries. Finally, based on the results of this analysis, this paper identifies geopolitical relations, the energy supply, technology and investment, and the demand for a transition to sustainable development as the main driving forces for China and Mongolia to collaborate on climate change mitigation under the BRI. Finally, the paper concludes that collaboration between the two countries is highly feasible.